PENGARUH LEMBAR KERJA SISWA (LKS) BERBASIS INKUIRI TERBIMBING DISERTAI MEDIA PHYSICSPOLY (MONOPOLI FISIKA) PADA MATERI ALAT-ALAT OPTIK TERHADAP MINAT DAN HASIL BELAJAR SISWA SMA DI JEMBER - Muhammad Naufal Ariiq; Bambang Supriadi; Subiki Subiki (FKIP Universitas Jember, 2019)
This research aimed to: 1) examined the effect of students worksheet (LKS) based on inquiry guidance along with physicpoly media (physics monopoly) at optical instrument material concerning with the learning outcomes of the students, and 2) examined the effect of students worksheet (LKS) based on inquiri guidance along with physicpoly media (physics monopoly) at optical instrument material concerning with the interest of the students. This research was experimental research that use research pattern post-test only control group design. The participants of this research were 11th grade science students at SMAN 1 Arjasa on the academic year 2018/2019. The sample was taken by cluster random sampling which determines XI IPA 3 class as experimental group and XI IPA 2 class as a control group. The data analysis technique was using independent sample T-test by SPSS program. The result of the independent sample t-test is the score learning outcomes and learning interest was different between the experimental class and the control class. The result shows that students worksheet (LKS) based on inquiry guidance was significantly influence concerning to the learning outcomes of the students. Whereas the analysis outcome on the learning interest of the students worksheet (LKS) based on inquiri guidance along with physicpoly media (physics monopoly) was not significantly influence concerning with learning interest of the students.Key Word: guided inquiry model, learning outcomes, learning interest, physicspoly